PENERAPAN PENGELOLAAN MANAJEMEN KELAS MELALUI PENDEKATAN GROUP PROCESS DI SD MUHAMMADIYAH 4 MALANG - Laila Efendi, Anggi; Diva Pujiaryanti, Anindya; Umniyya, Anisatul; Aditya Satriatama, Dandy; Anggia Rahmania, Dwi; Fatimatuzzahroh, Fatimatuzzahroh; Maisyaroh, Maisyaroh (Manajemen Pendidikan, 2023)
Classroom management is a skill that teachers must have in deciding, understanding, and utilizing class potential to create a conducive classroom atmosphere and achieve learning goals with the aim of creating a classroom atmosphere as a comfortable place for teaching and learning activities so that learning activities can run effectively and efficiently. . Class management at SD Muhammadiyah 4 Malang uses a democratic style which can be interpreted as a leadership style with efforts to develop one's capacity as a leader by directing subordinates to always be successful, open to accepting various suggestions and criticism from subordinates and prioritizing teamwork. The purpose of this article is to (1) explain the process of classroom management and learning and (2) explain the application of the group process approach. This article explains the results of observations made by researchers at the place used as the research location. In the research process, researchers used interview techniques, documents and observations to confirm the results of research conducted at SD Muhammadiyah 4 Malang. The management process discussed in this article is implementation, application and management problems which are expected to provide insight and provide input and suggestions for educational institutions to implement and optimize their services, especially in managing classroom management and learning in their schools. Apart from that, it is hoped that this article can provide an overview of the urgency of Class Management and the application of learning management in the successful management of an educational institution or school